How remote working increases the importance of positive leadership for employee vigor - Caniëls, Marjolein C. J. (Frontiers in Psychology, 2023)
Leadership is essential for creating a healthy and happy work environment for employees. Due to the COVID-19 pandemic, working remotely from home has become prevalent for many employees, which challenges leaders to reach out to their followers even if these followers are not physically at work. Drawing on positive psychology theories, the aim of this study is to investigate the relationship between positive leadership and psychological energy (i.e., vigor), and particularly the extent in which this relationship is affected by whether employees are working from home, as well as the tenure of the leader-follower relationship. To this end a two-wave time-lagged study design is used with a sample of 186 followers. Findings indicate that the effect of positive leadership on followers’ vigor is especially strong when employees work from home, and even more so when leaders and followers have a long lasting work relationship.